TINJAUAN YURIDIS TENTANG PENERAPAN RESTORATIVE JUSTICE PADA KASUS TINDAK PIDANA ANAK DI TINJAU DARI UU NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Erick Yehusy (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT Restorative Justice is the resolution of criminal cases involving offenders, victims, families perpetrator/victim, and other relevant parties to work together to find fair settlement with emphasis on restoring back to the original state, and not retaliation (Article 1 paragraph 6 of Law No. 11 Year 2012 on the Criminal Justice Child System). The basic process is done through the application Discretion (Police Authority) under Article 18 of Law No. 2 of 2002 on the Indonesian National Police and Diversion (Article 1 Paragraph 7 of Law No. 11 Year 2012 on the Criminal Justice Child System).The purpose in writing this law is to determine an equitable application of sanctions (Restorative Justice) against children in accordance with Law No. 11 Year 2012 on the Criminal Justice Child System which ensures certainty and legal protection of children and child away from judicial proceedings and sentencing are not good for the soul, dignity and child future. This research uses a technique that is normative juridical research or study procedure by referring to some of the principles of law, rule of law principles, and the principles of law relating to the substance of legislation that are general and specific. And do a bit of field observations in order to determine whether the concept has Restorative Justice applied in the handling of cases of children in conflict with the law. Data collection techniques used by collecting primary materials (Rule of Law) and secondary materials (Articles, web pages and books) as well as conducting interviews at the law enforcement officials involved (KAPOLRES Tenggarong and BABAS Samarinda).From the results of the study found that the application has been implemented through the Restotative Justice Police Discretion and Diversion Restorative Justice based approach. In the case of court settlement children almost everything can be resolved with the Restorative Justice exception of  severe cases.It is expected that the law enforcement approach should focus on Restorative Justice in each case the child for the realization of justice according to conscience (Moral Justice), attention to Justice Society (Social Justice) and consider the justice according to the law (Legal Justice) so that the achievement of the highest award for justice (Presice Justice). In completing Crime committed imprisonment child must be the Last Action (Ultimum Remedium). Keywords : (The Application of Restorative Justice, Child Protection)